Techno-economic Issues and Trade-offs for CO2 Purity in CCS Chains. (July 2017) - Eickhoff, Charles; Brown, Andy; Neele, Filip
Abstract: The IMPACTS project has the objective to develop the knowledge base of CO2 quality required for establishing norms and regulations to ensure safe and reliable design, construction and operation of CO2 pipelines and injection equipment, and safe long-term geological storage of CO2 . More specifically for this paper, the project sets out to reveal the impacts of relevant impurities in the CO2 stream on the design, operation and costs of the capture, transport and storage infrastructure and to provide recommendations for optimized CO2 quality through techno-economic assessments. The areas covered include corrosion from water content in the CO2 stream in combination with other impurities and the influences of impurities on transport, injection and storage processes and include estimates of the cost of measures to mitigate or prevent these impacts, or of adapting of CCS system design. A specifically designed CCS chain model is used to assess the impacts on a number of reference CCS chains, evaluating economic trade-offs to both understand the full-chain whole-life economics of certain CO2 impurities at different levels and then to potentially optimize a purity specification for various sets of circumstances.